Strengthening Financial Literacy through the Utilization of Financial Technology (Fintech) in Nurul Hidayah Women in Bandar Setia Village - Gea, Edi Zaman Berkat; Fitri, Nur Aisyah; Tobing, Ainun Sakinah L; Ajmilia, Qori Fadla; Sembiring, Robert Sanjaya; Absah, Yeni (PT FORMOSA CENDEKIA GLOBAL, 2024)
The strengthening of the times and the digital-I economic ecosystem encourages the transformation of the convention payment mode I to be digital-based. The purpose of the service is to provide an introduction and understanding of financial technology to the mothers of Nurul Hidayah Village in Bandar Setia Village. The method used is the socialization of material explanations, discussions and questions and answers, as well as giving gifts to mothers who understand this service material. After that, assistance was provided to Perwiritan Nurul Hidayah women to help use financial technology in transactions. The result of the service is that housewives can use financial technology in business activities and household activities. Housewives know how to take advantage of digital technology to enjoy financial services from various financial services.